Santa express - Thomas, Nobin; Mehrotra, Sonia; Vohra, Neharika, 1966-; Vatavwala, Sanket (London : Indian Institute of Management, Ahmedabad, 2024)
Three college friends-Rijin John, Vivek George and Arun Ghosh-came together to realise their decade-old dream of starting an enterprise. They launched Santa Express, an on-demand delivery service, for the pickup and delivery of handy and nonperishable goods in Kochi. Their idea of Santa serving customers was based partly on market research and intuition. However, lately, things have been difficult for Santa Express because of scaling issues, lack of an able/reliable workforce, funding, lack of long-term planning, co-founder’s shifting commitments and pricing. The time had come for the co-founders to decide whether to continue the venture or shut it down. The case poses a real-life situation for students considering or planning to establish new ventures. They will have to struggle with many of the questions facing Santa Express. Some students may be naturally inclined to throw caution to the wind and just go for it. Others may allow all the uncertainties and associated risks-real and imagined-to give them an excuse to take the safe road. This case allows the students to experience both the appealing facets and bothersome ambiguities of a start-up.
Description based on XML content.
Keywords: elektronické knihy; electronic books; New business enterprises -- Case studies; Express service -- Case studies